Eight Factors Bringing about Students’ Speaking Disfluency in Indonesia - Roi Boy Jon; Hilwa alfiani Fitri; Bambang Purnama (ITScience (Information Technology and Science), 2022)
English, among thousands of languages, is the most widespread and spoken by people around the world. Students in Indonesia, in particular, oftentimes measure their English mastery by evaluating to what extent their speaking fluency. It, thus, becomes challenging since they are not merely called for producing words but are required to apply the appropriate way of delivering the messages as well. With that in mind, this article aimed at figuring out the common challenges, which in turn lead to students’ speaking disfluency. Moreover, to unearth the answer to the objectives, this study applied qualitative library research which primarily focused on analyzing the secondary data such as online books, and articles as the sources. Finally, the challenges found encountered by the students to get fluency were affected by eight factors such as; Vocabulary, Grammar, Anxiety, Lack of Motivation, Learning Environment, Teachers’ Teaching Strategies, Self-Confidence, and Age. Besides, this article also proposed alternative solutions for both teachers and students in overcoming the issues. In a nutshell, the researcher hopes that this paper would benefit the upcoming researchers to be cited as an additional reference in English studies, and for teachers to be a guide to promote students’ speaking fluency.